Asbestiform fibers : nonoccupational health risks (National Academy Press, 1984)
More than 30 million tons of asbestos used in the United States since 1900 is present as insulation in offices and schools, as vinyl-asbestos flooring in homes, and in other common products. This volume presents an evaluation of the relation of these fibers to specific diseases and the extent of non-occupational risks associated with them.
Keywords: Asbestos fibers -- Toxicology.; Asbestos fibers -- Environmental aspects.; Risk management.; Asbestos -- adverse effects; Asbestosis -- etiology; Environmental Exposure; Risk Management; Fibres d'amiante -- Toxicologie.; Fibres d'amiante -- Aspect de l'environnement.; Gestion du risque.; Exposition (Toxicologie); risk management.; HEALTH & FITNESS -- Safety.; Asbestos fibers -- Environmental aspects; Asbestos fibers -- Toxicology; Risk management; Asbest; Faser; Gesundheitsgefährdung